Sebuah Analisis Wacana Kritis Lirik Lagu "Permission To Dance" Oleh BTS - Fernanda, Erikca Gardena; Widyahening, Ch. Evy Tri (ENGLISH RESEARCH JOURNAL, 2024)
Abstract: The objectives of this research were: 1) to identify the grammatical and lexical cohesion of song lyrics ‘Permission to Dance’ by BTS; 2) to identify the situational context of song lyrics ‘Permission to Dance’ by BTS, and; 3) to identify the cultural context of song lyrics ‘Permission to Dance’ by BTS. The research analyzed the grammatical and lexical cohesion of song lyrics “Permission to Dance” by BTS based on the theory of Cohesion in English by Halliday and Hasan. The result showed that there were various kind of grammatical cohesion found in the song lyrics such as references that includes persona references, demonstrative references, and comparative references; ellipsis; and conjunction. This research also analyzed the context of song lyrics “Permission to Dance” by BTS by using Language Context theory by Halliday and Hasan. There are two types of context analyzed: 1) situational context, contained the situation, the participants, and the objective of the lyrics; and 2) cultural context contained the cultural background of BTS as Korean citizen in producing “Permission to Dance” during the pandemic situation. Keywords: Discourse Analysis, Song Lyrics, Cohesion in Discourse, Situational Context, Cultural Context